Maybe for you - McLaughlin, Nicole (McLaughlin, Nicole. Whiskey and weddings novel., 2018)
After a year of mourning her fiancé, Alexis Parker has worked hard to rediscover what she wants out of life. Fresh out of the military and back stateside, her brother offers her a marketing job at the Stag Distillery. Ready for a new challenge, Alexis agrees to accompany her new co-worker Jake Cooper on a Stag cross-country promotional tour. He may have an infamous playboy reputation, but Alexis is surprised to find out that there is more to him than meets the eye. And she likes what she sees. . . Jake promised Alexis<U+2019>s brother that he<U+2019>d be an absolute gentleman. Of course, that was before he and Alexis hit the road, and they both agree that what Alexis<U+2019>s big brother doesn<U+2019>t know won<U+2019>t hurt him. The plan: to keep their fling confined to the RV, and everything will go back to normal once they head home. Things progress in ways neither of them could have imagined, and Jake realizes that he and Alexis make a perfect mix. Can he convince her that he<U+2019>s ready to shake things up and give true love a shot in Maybe for You?